Comparison of Newborn Hearing Screening in Well-Baby Nursery and NICU: A Study Applied to Reduce Referral Rate in NICU. - Pei-Chun Li; Wei-I Chen; Chih-Ming Huang; Ching-Ju Liu; Hsiu-wen Chang; Hung-Ching Lin (PLoS ONE, 2016)
OBJECTIVES:To determine whether newborn hearing screening in a well-baby nursery (WBN) and neonatal intensive care unit (NICU) nursery: 1) meet three targeted, screening, referral, and diagnostic follow-up rates; 2) compare the average age of diagnosis for infants admitted to the WIN and NICU; and 3) determine prevalence of hearing loss in neonatal population; and 4) try to find a practical newborn hearing screening time algorithm to reduce refer rate in NICU. MATERIALS AND METHODS:It examined 15,624 newborns in the WBN (13,676) and NICU (1948) screened for congenital HL using AABR. The variables analyzed in it were the screening rate, referral rate, follow-up rate, diagnostic rate and diagnostic age, prevalence rate, degrees of congenital bilateral HL. The study was approved by the hospital's institutional review board (13MMHISO23). RESULTS:The screening rates were 99.8% and 99.6% in the WBN and NICU groups, respectively, without significant difference. The referral rates were 0.7% and 2.8% in the WBN and NICU groups, with significant difference. Furthermore, the diagnostic follow-up rates were 76.7% and 89.1% in the WBN and NICU groups, without significant difference. The average initial diagnostic ages were 1.9 months and 3.8 months in the WBN and NICU groups, with significant difference. The prevalence of congenital bilateral hearing loss were 0.27% and 1.6% in the WBN and NICU groups, with significant difference. CONCLUSION:The screening, referral and follow-up rate in the WBN and NICU groups were equivalent to the quality indicators. For NICU group, screening and diagnostic follow up were performed later than those in WBN group; however the lower referral rate in our NICU group was successfully achieved in this study and can be applied clinically. The prevalence of congenital bilateral hearing loss was higher in the NICU group than in the WBN group.